UN Security council and Indo-Pak conflicts - "Arun,kumar singh" (Delhi, 1992)
The importance of Dr. Arun Kumar Singh's work "the UN Security Council and Indo-Pak Conflict" lies in that it is the first in-depth study of the role of the UN Security Council from the mid-1960's is resolving military conflicts between member states.
Keywords: United Nations-Security concil